Genetic Heterogenity Profile of Penaeus monodon Broodstock F1 Revealed by Mitochondria DNA-RFLP and RAPD - Bambang Widyo Prastowo; Rahayu Rahardianti; Evi Maftuti Nur; Arief Taslihan (Indonesian Journal of Biotechnology, 2007)
The genetic heterogeneity of Penaeus monodon broodstock F1 was evaluated using Restriction Fragment LengthPolymorphism (RFLP-mtDNA) and Random Amplified Polymorphic DNA (RAPD) analysis. The RFLP analysis wasconducted by amplifying 16SrDNA region and digested with restriction enzyme Nde II. According to the RFLPanalysis, heterogeneity value of P. monodon F1 broodstock population is 0,0422; male F1 population is 0,0613 andfemale F1 population is 0,1252. The primer OPA2 was used in RAPD analysis. According to the RAPD analysis,heterogeneity value of P. monodon F1 broodstock population is 0,0417; male F1 population is 0,0653 and female F1population is 0,1104. The results of this research showed that either RFLP or RAPD can be used as a family specificmarker for Penaeus monodon.Key words : Penaeus monodon, RFLP, RAPD, heterogeneity, genetic marker